Sources of change in CO2 emissions from energy consumption by industrial sectors in Malaysia - Abdullah Chik, Norlaila; Abdul Rahim, Khalid (2014)
Changes in the economic structure, energy consumption and awareness of the environmental impact have altered the intensity of CO2 emission from energy consumption in Malaysia. The objective of this study is to examine the sources of changes in CO2 emission from energy consumption by industrial sectors during 1991 to 2005 using IO-SDA model. Results show that export sector is the biggest generator of CO2 emissions caused by usage of CO2-intensive technologies and foreign demand for CO2-intensive products. In addition, high export earnings and positive growth rates are also sources of increased CO2 emissions through changes in the inputs used in the production activities. However, technology alone has not been strong enough to offset the negative environmental impact from changing export and consumption patterns in Malaysia. Our analysis shows that continuously increasing consumption and export that changes the input structure will continue to affect the environment. Thus, through technology improvement, particularly on inputs structure will reduce the CO2 emission somewhat. A policy to reduce CO2 emission should incorporate changes in the export as well as consumption patterns so that Malaysia’s commitment to reduce CO2 emissions by 40 percent in 2020 can be achieved.